Effects of Reduced Nitrogen Application on Dry Matter and Yield of Direct-Seeded Hybrid Rice in Low-Light Regions of Sichuan Province - Ran WANG; Qiange HE; Xiyuan WANG; Fei WANG; Zixiang TANG; Shengli ZHAO; Jun DENG; Jianming DING; Rongping ZHANG; Shenmin YAN; Peng MA (Guangdong nongye kexue)
【Objective】To clarify the responses of dry matter and yield of hybrid rice in the hilly areas of northwestern Sichuan to the reduction of nitrogen fertilizer application.【Method】'Jinlongyou 589' and 'Shenyouyuehesimiao' were selected as the experimental materials, and three different nitrogen fertilizer treatments were set up. They were the conventional nitrogen application rate of 180 kg/hm2 (N2), a 25% reduction in nitrogen application based on the conventional rate, that is, the nitrogen application rate of 135 kg/hm2 (N1), and no nitrogen application (N0, 0 kg/hm2) as the control. On this basis, chlorophyll, content, nitrate reductase (NR) activity, dry matter accumulation, and yield of hybrid rice under different nitrogen fertilizer reduction treatments were deeply analyzed.【Result】In terms of chlorophyll content, 'Shenyouyuehesimiao' was higher than' Jinlongyou 589'; while in terms of nitrate reductase (NR) activity, 'Shenyouyuehesimiao' was lower than 'Jinlongyou 589'. With the decrease of nitrogen application rate, the contents of chlorophyll a and chlorophyll b' and the NR activity of hybrid rice all showed a decreasing trend. The contributions of dry matter and post-heading dry matter accumulation to grains of 'Shenyouyuehesimiao' increased by 23.69% and 0.59% respectively compared with those of' Jinlongyou 589'. Treatment N1 led to a decrease in the dry matter accumulation of hybrid rice. Under treatment N2, the contributions of post-heading dry matter accumulation to grains and the population growth rate of 'Shenyouyuehesimiao' both reached the maximum values. The effective panicle number and 1000-grain weight of 'Shenyouyuehesimiao' were higher than those of 'Jinlongyou 589'. Meanwhile, the effective panicle number, filled grain number, seed setting rate, and 1000-grain weight of the two hybrid rice varieties all decreased with the reduction of nitrogen fertilizer application rate. In terms of yield, under treatment N2, the yield of 'Shenyouyuehesimiao' was 10 300.0 kg/hm2, and the yield of 'Jinlongyou 589' was 8 879.6 kg/hm2; under treatment N1, the yield of 'Shenyouyuehesimiao' was 9 818.72 kg/hm2, and the yield of 'Jinlongyou 589' was 8 495.03 kg/hm2. Compared with treatment N1, the yields of 'Shenyouyuehesimiao' and 'Jinlongyou 589' under treatment N2 increased by 4.9% and 4.5% respectively, but the difference was not significant.【Conclusion】In the hilly areas of northwestern Sichuan, controlling the nitrogen application level in the production of 'Jinlongyou 589' and 'Shenyouyuehesimiao' at 135 kg/hm2 is expected to achieve the coordinated development of yield improvement and green ecology.